Exploratory study on safety climate in Malaysia automotive manufacturing - Azizah, Endut (2011)
Safety climate scrutiny has given attention by the organization in increasing productivity and efficiency in the workplace. The purpose of this study was to determine the relationship between safety climate construct factors and safety climate. Safety climate measurement as developed by Vinodkumar and Bashi (2009) was used and distributed to the selected respondent in national automotive manufacturing plant, whereby 195 respondents were participated in data collection. Internal consistency of six safety construct factors and correlation between safety construct factors and safety climate were validated using reliability analysis and Pearson correlation, respectively. The survey instrument scores had acceptable overall internal consistency (α = 0.913). The correlation analysis indicated that only two factors in safety construct factors have significant with safety climate. Both of factors are enforcement of regulation and procedure of safety and safeness of work environment. The finding of this study provides a useful framework for the organization in practicing safety climate. Organization should pay more attention to enforcement of regulation and procedure of safety as well as safeness of work environment in order to improve safety climate.